2003
DOI: 10.1091/mbc.e02-08-0503
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Caveolin-1 Gene Expression Accelerates the Development of Dysplastic Mammary Lesions in Tumor-Prone Transgenic Mice

Abstract: Caveolin-1 is the principal structural component of caveolae microdomains, which represent a subcompartment of the plasma membrane. Several independent lines of evidence support the notion that caveolin-1 functions as a suppressor of cell transformation. For example, the human CAV-1 gene maps to a suspected tumor suppressor locus (D7S522/7q31.1) that is frequently deleted in a number of carcinomas, including breast cancers. In addition, up to 16% of human breast cancers harbor a dominant-negative mutation, P13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
101
2
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 136 publications
(113 citation statements)
references
References 55 publications
9
101
2
1
Order By: Relevance
“…CAV1-null mice show a striking increase in the frequency and size of multifocal dysplastic lesions in mammary grands, with the nuclei and the nuclei of mammary grand cells showing anaplastic characteristics with increased mitotic figures (Williams et al, 2003). This suggests that CAV1-mediated interactions between myoepithelial cells and the rest of mammary gland may play an important role in oncogenesis.…”
Section: Discussionmentioning
confidence: 97%
“…CAV1-null mice show a striking increase in the frequency and size of multifocal dysplastic lesions in mammary grands, with the nuclei and the nuclei of mammary grand cells showing anaplastic characteristics with increased mitotic figures (Williams et al, 2003). This suggests that CAV1-mediated interactions between myoepithelial cells and the rest of mammary gland may play an important role in oncogenesis.…”
Section: Discussionmentioning
confidence: 97%
“…Secondly, genetic disruption of both Cav-1 alleles results in premature development of the lobulo-alveolar compartment during pregnancy (57). Finally, complete absence of Cav-1 accelerates the appearance of oncogene-induced dysplasias (pre-malignant lesions) in the mammary epithelium (28). Although these results are suggestive, it remains unknown whether loss of caveolin-1 has any consequences for the development of advanced and aggressive mammary tumors and resulting metastatic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Animal protocols used for this study were approved by the AECOM Institute for Animal Studies. Cav-1-null mice and MMTV-PyMT transgenic mice (strain 634) were generated as previously described (8,28). All the mice used in this study were in the FVB/N background.…”
Section: Materials and Expressionmentioning
confidence: 99%
“…On the other hand, the expression levels of both ER␣ and caveolin-1 were reduced, as expected in more advanced tumor lesions ( Figure 5A). 21,29 Cytokeratin protein levels were not affected by the treatment ( Figure 5D). Moreover, normalization with cytokeratin indicated that caveolin-1 and ER␣ protein levels were reduced 1.5-and 1.3-fold, respectively, in tumors obtained from animals fed a Western diet.…”
Section: Dietary Cholesterol Is Associated With a Protein Expression mentioning
confidence: 95%
“…21 Whole mounts were digitally photographed with a ruler, and total area measurements for the dysplastic lesions were quantified using Image J software. 22 …”
Section: Whole-mount Analysis Of Mammary Glandsmentioning
confidence: 99%